Determination of bosutinib in mice plasma and tissue by UPLC-MS/MS and its application to the pharmacokinetic and tissue distribution study. Issue 21 (6th October 2015) - Wang, Linxia; Tang, Luming; Zheng, Yi; Pan, Guoquan; Zhu, Wei; Pan, Chenwei; Zhu, Lihe
Abstract : A sensitive and rapid ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method was developed to determine bosutinib in mice plasma and tissue using diazepam as the internal standard (IS). Abstract : A sensitive and rapid ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method was developed to determine bosutinib in mice plasma and tissue using diazepam as the internal standard (IS). Sample preparation was accomplished through a protein precipitation procedure with acetonitrile. The analyte and IS were separated on an Acquity UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm) with the mobile phase of acetonitrile and 0.1% formic acid in water with gradient elution at a flow rate of 0.40 mL min −1 . The detection was performed on a triple quadrupole tandem mass spectrometer equipped with electrospray ionization (ESI) by multiple reaction monitoring (MRM) of the transitions at m / z 530.3 → 141.1 for bosutinib and m / z 285.2 → 193.1 for the IS. The linearity of this method was found to be within the concentration range of 5–3000 ng mL −1 with a lower limit of quantification of 5.0 ng mL −1 . Only 3.0 min was needed for an analytical run. The method herein described was superior to previous methods and was successfully applied to the pharmacokinetic and tissue distribution study of bosutinib in mice after oral administration.